APPLICATION Archiving IN MULTIMEDIA DEPT. AT KPK USING MICROSOFT VISUAL BASIC 6.0 - Ivan Yudhistira; Yulina, SKom. MMSI Yulina, SKom. MMSI (Jurnal Sistem Informasi, 2006)
Information needs of current computer system is something very important in supporting the operations of a multimedia field in the Commission institute, which is a computer information system is very efficient and effective in its use. This application aims to speed up filing a report for it. Which have been implemented by the team with the help of the Commission Multimedia computer media through Microsoft Visual Basic 6.0. so that the data processing will be faster and more accurate and certainly will improve the efficiency of work.